Palm Date, Phoenix dactylifera, L. Extract Effect on Spermatozoa Quality of Giant Grouper, Epinehelus lanceolatus (Bloch, 1970) after Frozen - Abinawanto, . (Advanced Aspects of Engineering Research Vol. 2, 2021)
Palm juice, known by several local names, is an alcoholic beverages gotten naturally from the sap of various species of palm tree such as the Palmyra, date palms and coconut palms. It is known by various names in different regions and is common in various parts of Asia. Therefore, this study aims to determine the combined effect of 6% glycerol with different concentrations of palm date juice on the quality of spermatozoa of the giant grouper, Epinephelus lanceolatus (Bloch, 1970), post-frozen storage. The giant grouper semen was obtained using the hand stripping method, and the diluent used is a mixture of marine fish ringers, 6% glycerol, and different concentrations of palm date extract (5%; 10%; 15%; 20%; and 25%). Furthermore, equilibration was carried out at 4 ºC for 10 minutes, and the sperm storage was carried out at -20°C for 48 hours. Thawing was carried out at 45 ºC for 30 seconds. The evaluation of semen was carried out macroscopically (color, volume, and pH) and microscopically (motility, viability, and abnormalities) as well as the ability to fertilize the eggs of the tiger grouper, Epinephelus fuscogutatus (Forskal, 1775). Based on the results of the ANOVA test followed by the Tukey test, there was a significant difference (p <0.05) in the motility, abnormalities, and the ability of post-frozen giant grouper spermatozoa to fertilize, but this had no significant effect (p> 0.05) on spermatozoa viability. The results showed that the treatment of 10% palm date juice was the optimum concentration because it showed the average percentage value of motility, and the highest fertility was 76.70 ± 1.54% and 66.25 ± 3.23%, and the lowest abnormality was 21.53 ± 0.84%, meanwhile, the percentage of viability was 77.67 ± 5.78%.